Financiamento cultural no Brasil contemporâneo - Frederico Augusto Barbosa Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This text discusses the dynamics of cultural funding in the Brazilian federal government from 1995 to 2013. It describes the historical context and faces some of the arguments present in the public debate on the principles that can justify reforms in the administration of culture and reconfiguration of the stock financing model public in the area. Moreover, it faces discussion of these general ideas in the light of the plurality of criteria and instruments used by the public administration. The dialectic between general ideas, tools and practices allows for more precise delimitation between the financing paradigms or models.
Keywords: Z18; 330; financing of public policies; cultural policies; cultural spending